Identification and Expression Profile of CYPome in Perennial Ryegrass and Tall Fescue in Response to Temperature Stress - Tao, Xiang; Wang, Ming-Xiu; Dai, Ya; Wang, Yan; Fan, Yan-Fen; Mao, Ping; Ma, Xin-Rong (Frontiers in Plant Science, 2017)
Plant cytochrome P450s are involved in a wide range of biosynthetic reactions that generate various biomolecules, including a variety of defensive compounds. Perennial ryegrass (Lolium perenne) and tall fescue (Festuca arundinacea) are two major species of turf and forage grasses that usually experience low temperature below −10°C and high temperature over 38°C around the world. In this study, we re-analyzed transcriptome of perennial ryegrass and tall fescue treated with heat and cold stress. Thus, we can evaluate P450 composition in these species and confirm whether P450 genes response to temperature stress. We identified 277 and 319 P450 transcripts with open reading frames larger than 300 bp, respectively. These P450 transcripts were mainly classed in the CYP71, 51, 94, 89, 72, and 734 families. In perennial ryegrass and tall fescue, a total of 66 and 62 P450 transcripts were up-regulated, and 65 and 117 transcripts were down-regulated when subjected to heat stress, respectively. When exposed to cold stress, 60 and 73 transcripts were up-regulated, and 59 and 77 transcripts were down-regulated in perennial ryegrass and tall fescue. Among these differentially expressed transcripts, 64 and 87 of them showed expression level changes that followed the same trend, and these temperature-responsive genes primarily belong to the CYP71, 72 and 99 families. Besides, heat and cold stress altered phenylalanine and brassinosteroid involved P450 transcripts in perennial ryegrass and tall fescue. P450 transcripts involved in the metabolism of these compounds showed a strong response to heat and/or cold stress, indicating that they likely play important roles in temperature acclimation in these two species. The CYPome provide a genetic base for the future functional studies, as well as genetic studies that may improve stress tolerance for perennial ryegrass and tall fescue to extreme temperature.